Barbie's wet dream a diorama of gay men in the female fantasy - Tiapson, Iris Dominique O. (College of Fine Arts, University of the Philippines Diliman, 2017)
Beautiful, well-built yet slender boys in the arms of another equally attractive male have always been my aesthetic. As such, I was inspired to create works that interpret males in a homoerotic context. Through my thesis, I aim to produce a diorama based on a dollhouse which acts an outlet, catering to females whose fantasies primarily involve the male form and homoerticism. The imagery, techniques, mediums and objects are selected based on a selection of referenced literature, artworks as well as personal taste, and history. These are then utilized in a way which is a manner that most effectively represents the intended design and content.